2007
DOI: 10.1089/jop.2006.0091
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after Topical Nonpreserved Methylprednisolone Therapy for Keratoconjunctivitis Sicca in Sjögren's Syndrome

Abstract: Topical nonpreserved methylprednisolone pulse therapy proved to be a safe, effective long-term treatment of improving subjective and objective dry eye factors in KCS patients with Sjögren's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 8 publications
(10 reference statements)
1
28
0
1
Order By: Relevance
“…The treatment led to significantly improved tear break-up time (BUT) and Schirmer test results at the end of the treatment period and drug-free remission for a mean duration of 56.6 weeks and 20.8% recurrences. The clinical improvement was associated with an increased number of conjunctival goblet cells as assessed by impression cytology (23).…”
Section: Topical Treatmentsmentioning
confidence: 94%
“…The treatment led to significantly improved tear break-up time (BUT) and Schirmer test results at the end of the treatment period and drug-free remission for a mean duration of 56.6 weeks and 20.8% recurrences. The clinical improvement was associated with an increased number of conjunctival goblet cells as assessed by impression cytology (23).…”
Section: Topical Treatmentsmentioning
confidence: 94%
“…In the setting of dry eye disease, topical corticosteroids have been shown to decrease corneal fluorescein staining, improve tear break up time, and improve Schirmer 1 testing [18,19]. A recurrence of signs of keratoconjunctivitis sicca may recur after stopping topical corticosteroids [19].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…In the setting of dry eye disease, topical corticosteroids have been shown to decrease corneal fluorescein staining, improve tear break up time, and improve Schirmer 1 testing [18,19]. A recurrence of signs of keratoconjunctivitis sicca may recur after stopping topical corticosteroids [19]. Lowpotency topical corticosteroid treatment with fluoromethalone (FML) in conjunction with artificial tears when compared to artificial tears alone and combination artificial tears and flurbiprofen (a topical nonsteroidal) has been shown to not only improve fluorescein and rose bengal staining but also demonstrate higher numbers of goblet cells on impression cytology in a randomized trial (involving Sjögren's syndrome and non-Sjögren's participants) [20].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Numerous studies have concluded topical or systemic corticosteroid therapy may have several benefi ts in the treatment of moderate to severe dry eyes. 59,87,88 For instance, in one study reviewing the effi cacy and side effects of topical nonpreserved corticosteroid therapy for treatment of severe KCS with SS, topical nonpreserved methylprednisolone was found to be effective for severe KCS. However, it has been also emphasized that careful monitoring is mandatory in these cases because of steroid-related complications.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
“…87 Similar results were obtained from another study that evaluated the prevalence of long-term recurrence after topical nonpreserved methylprednisolone pulse therapy for the treatment of KCS with SS. 88 In an experimental dry eye model, the mechanisms of topical methylprednisolone and doxycycline in the treatment of infl ammation were described. 59 According to that study, both agents reduced expression and activity of MMP-9, decreased levels of infl ammatory cytokines transcripts and reduced activation of MAPKs in the corneal epithelium.…”
Section: Corticosteroid Therapymentioning
confidence: 99%